Parametric design and multi-objective optimization of a 6,500 TEU container ship - Priftis, Alexandros (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Ναυπηγών Μηχανολόγων Μηχανικών, 2015)
The introduction of new and strict regulations by international organizations, as well as the constant endeavor of shipping companies for economic growth has led the shipbuilding industry to the introduction of new and cost-efficient designs in various types of merchant ships. In particular, container carriers, which are responsible for the shipping of millions of containerized goods every year, have recently started gaining in popularity among the ship owners around the globe. Hence, the competition between the international shipbuilders is getting stronger day by day, with each shipyard striving to offer the best container ship design that complies with both the existing and the imminent rules, yet without compromising the overall efficiency. In order to improve a design, naval architects are encouraged to make proper use of CAD/CAE systems, which offer not only high convenience -by producing valuable results in short time- but also the much desired integration of design, engineering and manufacturing in a seamless operation. In the recent years, the optimization process has been quite popular in the field of engineering. As a result, software companies have excelled their products in such level that the consideration of design optimization in the design process has become of great value. In this respect, our project deals with a case study of a mid-sized, 6,500 TEU container vessel. Firstly, the modeling of the ship, along with the creation of several subsystems that provide the necessary indicators takes place. Afterwards, an iterative optimization process begins, which results in a number of optimal designs, as far as certain objectives are concerned. Finally, an optimal design is selected, as a representative of the whole procedure. For this purpose, a powerful CAD/CAE software is used, CAESES/Friendship-Framework, which allows the user to create the parametric model, execute hydrostatic calculations and run multiple optimization cycles using various methods included in the software.